Hard water can be softened by atomization - Kasumi, Mayu; Yamashita, Takatoshi; Kubo, Kazuhiro (Food Science and Technology Research, 2023)
Hard water is softened because its use in everyday life can cause various problems in the living environment. However, existing water-softening methods have a number of drawbacks. Here we examined a new water-softening method involving atomization. Three concentrations of calcium-based synthetic hard water and a commercial natural hard water were prepared. Each hard water was sprayed into the atmosphere at 1 MPa from an atomization nozzle and then collected. Part of the collected water was recirculated, and the atomization treatment was continued. After the treatment, a white precipitate and fine bubbles were generated, the Ca2+ concentration and electrical conductivity decreased, and the pH increased. Then over time, the white precipitate increased slowly and the Ca2+ concentration decreased until finally it almost fell within the recommended range. This water-softening phenomenon was thought to be due to expansion of the gas-liquid interfacial area and generation of fine bubbles with atomization. This method is extremely simple and expected to show high versatility.